2012
DOI: 10.2478/v10298-012-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Fertilizer and Crop Residue on Soil Fertility in the Moldavian Plateau

Abstract: în perioada ianuarie-august. După 46 de ani de experimentare, în rotaţia culturilor mazăre-grâu-porumb, conţinutul de carbon organic din sol a scăzut cu 22,3% (4,2 g/kg sol) la varianta martor nefertilizată şi cu 14,4% (2,7 g / kg sol) la doza de N 120 P 80 . La culturile de grâu şi porumb, cantităţile de azot consumate de buruieni au fost cuprinse între 7 şi 9,5 kg / ha la toate variantele. Aplicarea unor doze moderate de îngrăşăminte minerale (N 80 P 60 ), împreună cu 6 t/ha paie de grâu sau cu 40 t/ha gunoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In agreement, Rushemuka et al [7] reported that the favorable response of good soils to FYM application was attributed to supply of soil nutrients. Additionally, the positive impacts of soil organic matter in storing and supplying of nutrients were also described [43][44][45]. Furthermore, a significantly higher mean yield of rice from black soils (i.e., perceived as fertile by farmers) compared to other soil types was stated [14].…”
Section: Farmers Soil Types and Their Productivitymentioning
confidence: 99%
“…In agreement, Rushemuka et al [7] reported that the favorable response of good soils to FYM application was attributed to supply of soil nutrients. Additionally, the positive impacts of soil organic matter in storing and supplying of nutrients were also described [43][44][45]. Furthermore, a significantly higher mean yield of rice from black soils (i.e., perceived as fertile by farmers) compared to other soil types was stated [14].…”
Section: Farmers Soil Types and Their Productivitymentioning
confidence: 99%